2009
DOI: 10.1002/cncr.24392
|View full text |Cite
|
Sign up to set email alerts
|

Does hormone treatment added to radiotherapy improve outcome in locally advanced prostate cancer?

Abstract: BACKGROUND:To quantify the magnitude of benefit of the addition of hormone treatment (HT) to exclu-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 37 publications
2
36
0
10
Order By: Relevance
“…This finding has resulted in decreased incidence and severity of rectal adverse events [3,4]. It has also been confirmed that combining HT with EBRT significantly improved not only biochemical control but also survival outcomes compared with EBRT alone [5,6]. These benefits were observed with both short-term (3-6 months) and long-term (>1 year) HT [5].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…This finding has resulted in decreased incidence and severity of rectal adverse events [3,4]. It has also been confirmed that combining HT with EBRT significantly improved not only biochemical control but also survival outcomes compared with EBRT alone [5,6]. These benefits were observed with both short-term (3-6 months) and long-term (>1 year) HT [5].…”
Section: Discussionsupporting
confidence: 50%
“…Meanwhile, the survival benefits of adding hormonal therapy (HT) to the standard doses of EBRT had also been confirmed [5,6]. The survival benefit of combining HT with EBRT over EBRT alone was observed in both…”
Section: Introductionmentioning
confidence: 94%
“…The EORTC trial 30891 randomised 985 patients with cT1-4, non-metastatic PCa patients unsuitable for curatively intended treatment and found an OS benefit of immediate castration compared to deferred therapy [20]. Finally, two meta-analyses of randomised trials have shown a PCa-specific and OS benefit of adding ADT to external beam radiotherapy with curative intent [21,22]. These studies advocate in favour early castration-based therapy in patients with locally advanced or lymph node positive PCa.…”
Section: Discussionmentioning
confidence: 95%
“…Después de este estudio otros confirman sus resultados [9][10][11][12][13][14] , quedando constancia de la utilidad del tratamiento combinado. Widmark et al…”
Section: Discussionunclassified